2009
DOI: 10.1111/j.1749-6632.2009.04707.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Mitochondria and Relocation of the Apoptosis‐Inducing Factor during Apoptosis

Abstract: During apoptosis, apoptosis-inducing factor (AIF) is released from the mitochondrial intermembrane space to the cytosol and to the nucleus. We analyzed AIF in HeLa cells driven to apoptosis by either etoposide or actinomycin D, and we observed changes in the structure and function of mitochondria as well as the translocation of cytochrome c and AIF from mitochondria to the nucleus in early apoptosis. In cells with fragmented chromatin (i.e., in late apoptosis), the immunolabeling for AIF appeared to be distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…As previously published, we observed that AIF translocates from mitochondria to the nucleus irrespectively of the applied apoptogenic stimuli, including etoposide, actinomycin D, carboxamides, cisPt, inhibitors of Na + /H + exchangers and photosensitizers [4,23,24,27]. This event is widely reported to occur in early-mid phases of the apoptotic program.…”
Section: Mitochondriasupporting
confidence: 54%
See 1 more Smart Citation
“…As previously published, we observed that AIF translocates from mitochondria to the nucleus irrespectively of the applied apoptogenic stimuli, including etoposide, actinomycin D, carboxamides, cisPt, inhibitors of Na + /H + exchangers and photosensitizers [4,23,24,27]. This event is widely reported to occur in early-mid phases of the apoptotic program.…”
Section: Mitochondriasupporting
confidence: 54%
“…Accumulating evidence supports the notion that during apoptosis AIF is released from mitochondrial intermembrane space to the cytosol and moves to the nucleus, where it promotes chromatin condensation and high molecular weight DNA degradation [26]. The changes in AIF localization have been monitored by light and electron microscopy by different groups, including ours, often coupling its analysis to a careful evaluation of mitochondria morphology [4,26,27]. …”
Section: Mitochondriamentioning
confidence: 99%
“…One of the examples is apoptosis‐inducing factor (AIF), which is released from the mitochondrial IMS to the cytosol and to the nucleus in the presence of many antibiotics. In cancer cells, genistein, tetracycline analogue COL‐3, actinomycin D, antimycin A, and doxorubicin induced apoptosis coupled with reduction of ∆Ψm, release of cytochrome c to cytosol, translocation of AIF to nucleus, activation of caspase‐3, increase of Bax expression, and generation of DNA fragmentation.…”
Section: Antibiotics and Cancer Therapymentioning
confidence: 99%
“…Cytochrome c release from the mitochondria and translocation to the nucleus is a hallmark of early events that initiates the intrinsic apoptotic cascade (55). Therefore, pulmonary fibroblasts from AhR Ϫ/Ϫ or AhR ϩ/ϩ mice were treated with CSE, and cytochrome c release was determined by immunofluorescence.…”
Section: Panel V) However In Ahrmentioning
confidence: 99%